The Many Lives of Victorian Fiction - Mangum, Teresa (Romanticism and Victorianism on the Net, 2009)
AbstractCan Victorian literature speak to non-academic publics of the twenty-first century as it did to “common readers” of the past? This essay discusses several experiments in which faculty members, graduate students, and undergraduates find creative means to engage local as well as university communities in the study of Victorian and Edwardian texts. In particular, the essay considers the power of public performance—in this case of Elizabeth Robins’s suffrage play, The Convert—to inspire collective “reading,” interpretation, and reflection on the future as well as the past.